Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00423-010-0669-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body image on patients’ attitude towards conventional, minimal invasive, and natural orifice surgery

Abstract: Patients with an NBI tend towards scarless surgery and are willing to accept increased operative risk and to spend additional money for improved postoperative cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…A variety of emerging factors are influencing the delivery of health care in the United States as well as the practical challenges faced by surgeons on a daily basis. These include strong popular interest in the newest minimally invasive techniques 1‐3 such as laparoscopic, 4 endoscopic, 5 and robotic approaches; 6 evidence that blood transfusions may have negative effects 7 on cost 8 as well as surgical morbidity 9 and mortality 10 particularly when extended‐storage banked blood is used; 11,12 emergence of several novel anticoagulation modalities such as direct thrombin or Factor Xa, inhibitors that do not require frequent monitoring, 13 but which are difficult to quickly reverse; 14 larger numbers of older patients now considered reasonable candidates for an increasing variety of operative procedures 15‐19 with a simultaneous increase in the proportion of the population considered elderly; 20 and finally, need for cost containment particularly in view of rapidly increasing health care expenses and restricted economic growth 21…”
Section: Introductionmentioning
confidence: 99%
“…A variety of emerging factors are influencing the delivery of health care in the United States as well as the practical challenges faced by surgeons on a daily basis. These include strong popular interest in the newest minimally invasive techniques 1‐3 such as laparoscopic, 4 endoscopic, 5 and robotic approaches; 6 evidence that blood transfusions may have negative effects 7 on cost 8 as well as surgical morbidity 9 and mortality 10 particularly when extended‐storage banked blood is used; 11,12 emergence of several novel anticoagulation modalities such as direct thrombin or Factor Xa, inhibitors that do not require frequent monitoring, 13 but which are difficult to quickly reverse; 14 larger numbers of older patients now considered reasonable candidates for an increasing variety of operative procedures 15‐19 with a simultaneous increase in the proportion of the population considered elderly; 20 and finally, need for cost containment particularly in view of rapidly increasing health care expenses and restricted economic growth 21…”
Section: Introductionmentioning
confidence: 99%
“…Application of scar-reducing or scarless operations seems to be a modern trend which is mostly preferred by young and educated patients (14,15). Moreover, patients with a negative body image tended to receive no scar surgery and were willing to accept increased surgical risks and higher costs to improve the cosmetic outcome (16). There is also evidence that less invasive surgery increases both the body image and cosmesis which was shown in a randomized controlled trial comparing laparoscopic single-port versus three-port appendectomy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Patient's preference on scarless concept may be influenced by age, gender, and surgical/endoscopic history at the cost of increased personal risk. A recent study [73] found that patients with "negative body image" favour scar less concept accepting increased operative risk [56]. Umbilicus hides the scar of surgical insult in SILS.…”
Section: Methodological Righteousness Sans Honestymentioning
confidence: 99%